2017
DOI: 10.11606/s1518-8787.2017051006543
|View full text |Cite
|
Sign up to set email alerts
|

Recent illicit drug use among psychiatric patients in Brazil: a national representative study

Abstract: OBJECTIVE To estimate factors associated to illicit drug use among patients with mental illness in Brazil according to gender.METHODS A cross-sectional representative sample of psychiatric patients (2,475 individuals) was randomly selected from 11 hospitals and 15 public mental health outpatient clinics. Data on self-reported illicit drug use and sociodemographic, clinical and behavioral characteristics were obtained from face-to-face interviews. Logistic regression was used to estimate associations with recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…In Brazil, a study found higher rates of both past-year (11•4%) and lifetime (25•4%) illicit drug use among patients with mental ill health. 41 The EMR was excessively high in young people in our study supporting previous findings. 25 The persistent gap in life expectancy for those with severe mental illness should be viewed as an example of discrimination, and points to a need for increased equity among those living with mental illness compared with the general population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In Brazil, a study found higher rates of both past-year (11•4%) and lifetime (25•4%) illicit drug use among patients with mental ill health. 41 The EMR was excessively high in young people in our study supporting previous findings. 25 The persistent gap in life expectancy for those with severe mental illness should be viewed as an example of discrimination, and points to a need for increased equity among those living with mental illness compared with the general population.…”
Section: Discussionsupporting
confidence: 91%
“…42 People with severe mental illness are exposed to worse cultural, sociological, and economic factors, such as less healthy lifestyles, poorer socioeconomic circumstances, and the social consequences of mental illness. 25,28,41,43 Additionally mortality in people with mental disorders is likely to be related to various causes, including behavioural factors and patterns in modifiable risk factors, access to and quality of health-care systems, and social determinants of health, such as poverty and lack of social support. 6,7 This study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In Arab countries, several studies show the prevalence of SU is rising, including Saudi Arabia ( Alblooshi et al, 2016 ; Ibrahim et al, 2018 ; Al-Alawi and Shaikh, 2018 ). Apparently, recent evidence shows the association of SU among persons with mental illness ( Nahas et al, 2017 ; Nielsen et al, 2017 ). Studies show that the prevalence of SU in persons with mental illness has higher rates compared with the general population and in particularly of amphetamines, alcohol and cannabis ( Nielsen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The literature shows that the population with MD presents a greater risk to the development of communicable diseases and related to the poverty, like Tuberculosis (TB) than other health conditions (3) . The various MD due to psychoactive substance abuse, such as Illicit Drugs, Alcoholism and Smoking have been being associated with TB illness (4)(5)(6)(7)(8)(9) . Different explanations are found in the literature for such a cellular association of immunohistochemical reactions, gender differences, behavioral characteristics, lifestyle and work, and unhealthy environments (10) .…”
Section: Introductionmentioning
confidence: 99%